2022
DOI: 10.3390/coatings12091253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Airflow Disturbance on the Uniformity of Spin Coating Film Thickness on Large Area Rectangular Substrates

Abstract: Spin coating is widely used to form a uniform film on a solid substrate. Airflow disturbance has been considered as one of the most influential factors of film thickness, especially for spin coating on large area noncircular substrates. However, the exact mechanism of airflow disturbance influence, such as air shear force effect or indirect effects on evaporation, so far, remains ambiguous. In this work, the influence mechanism of airflow disturbance on film uniformity on large rectangular substrates is studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our previous studies, this photosensitive material was made by modifying the hydroxyl group of each dextrin with acrylate, a photosensitive group, while maintaining water solubility. This material was applied by spin-coating [19] on a silicon wafer, exposed with a mask contact exposure system, and developed with water to evaluate sensitivity, etching resistance, and coating strength. In the microfabrication evaluation, it was found that the performance varied depending on the bonding mode.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, this photosensitive material was made by modifying the hydroxyl group of each dextrin with acrylate, a photosensitive group, while maintaining water solubility. This material was applied by spin-coating [19] on a silicon wafer, exposed with a mask contact exposure system, and developed with water to evaluate sensitivity, etching resistance, and coating strength. In the microfabrication evaluation, it was found that the performance varied depending on the bonding mode.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been observed that the fluorinated materials obtained by the incorporation of fluorinated compounds in functional materials (e.g., blended composites, hydrogels, and functionalized surfaces), have been used in various applications, such as imaging [1], electronics/optoelectronics [2,3], conductors [4,5], surface coatings [6,7], and the automotive industry [8]. Different functional silica materials were prepared by various methods such as the sol-gel method [9], centrifugal casting [10], liquid-phase deposition [11], and spin-coating [12]. The sol-gel method has been widely used to fabricate organic-inorganic hybrid materials based on fluorinated compounds, and hydrophobic organic thin films due to their advantages such as simple processing, controllability, versatility, feasibility, low-temperature processing, lower maintenance, and repeatability.…”
Section: Introductionmentioning
confidence: 99%